A PROFILE OF BIOLOGY AND SCIENCE TEACHER’S KNOWLEDGE ABOUT LOCAL WISDOM IKAN LARANGAN IN WEST SUMATERA - Ilhami, Aldeva; Riandi, .; Sovia, Siska Umi (PUPIL: International Journal of Teaching, Education and Learning, 2019)
Indonesia has many cultures such as Ikan larangan in West Sumatra. Ikan larangan area is a local wisdom of Minangkabau community that has conservation value of aquatic resources. More than 80% areas of West Sumatra have ikan larangan areas that are still preserved by the local community. Science and Biology subjects have environmental and conservation learning materials. The aims of this research are to find out about the knowledge of Science and Biology teachers about the local wisdom of ikan larangan and to find out about the extent of the use of the local wisdom in Science and Biology teaching and learning process. Respondents in this research are Biology teachers in Senior High School, Science teachers in Junior High School, and Science teachers in Primary School. The number of respondents is 31. The sampling technique used is purposive sampling. The research method used the questionnaire as the data collecting instrument. The results show that the knowledge of Science and Biology teachers about the local wisdom of ikan larangan is 81%. However, the level of using of the local wisdom in Science and Biology teaching and learning process is still relatively low at 29%.